Glottic regeneration with a tissue‐engineering technique, using acellular extracellular matrix scaffold in a canine model†. (8th January 2014) - Kitamura, Morimasa; Hirano, Shigeru; Kanemaru, Shin‐ichi; Kitani, Yoshiharu; Ohno, Satoshi; Kojima, Tsuyoshi; Nakamura, Tatsuo; Ito, Juichi; Rosen, Clark A.; Gilbert, Thomas W.
Abstract: Acellular extracellular matrix scaffold derived from porcine urinary bladder (UBM) is decellularized material that has shown success for constructive remodelling of various tissues and organs. The regenerative effects of UBM were reported for the tympanic membrane, oesophagus, trachea, larynx, pleura and pericardium in animal studies, with promising results. The aim of this study was to investigate the regenerative effects of UBM on hemilarynx, using a canine model. A left partial hemilaryngectomy was performed and the surgical defects were reconstructed by insertion of UBM scaffold. Although local infection was observed in one dog in 1 week after implantation of the scaffold, all dogs showed good re‐epithelialization with minimum complication in 1 month. The effect of regeneration of the larynx was evaluated 6 months after the operation. The excised larynx experiments were performed to measure phonation threshold pressure (PTP), normalized mucosal wave amplitude (NMWA) and normalized glottal gap (NGG). The results of the measurements showed that PTP was normal or near normal in two cases and NMWA was within normal range in three cases, although there were individual variations. Histological examination was completed to evaluate structural changes in the scaffold with the appearance of the new cartilaginous structure. However, the regenerated vocal fold mucosa was mostly scarred. The UBM scaffold has shown to be biocompatible, biodegradable and useful for tissue regeneration of the hemilarynx, with possible restoration of function of the vocal fold. The vocal fold mucosa was scarred, which is the next challenge to be addressed. Copyright © 2014 John Wiley & Sons, Ltd.